Modern management of malignant pleural effusions - Mercer, R; Corcoran, J; Rahman, N (Lippincott, Williams & Wilkins, 2016)
The development of a malignant pleural effusion (MPE) is diagnostic of advanced incurable cancer, and is seen with increasing frequency as the population ages and patients with malignancy survive for longer after the diagnosis as a result of advances in oncological therapies. MPE is frequently associated with significant symptoms including dyspnea, malaise, and cough that have a negative impact on a patient's quality of life. Treatment is generally palliative, with the median survival after diagnosis varying from 3 to 12 months. There has been considerable progress in recent years with respect to the management of MPE, and both patients and clinicians are now faced with a wide range of therapeutic interventions, each of which has its own advantages. This review article aims to summarize the evidence that underpins our current understanding of MPE and its treatment, and offer an insight into how ongoing research may further impact patient care in the future.